Fatigue Resistance of Low Alloy Steel after Shot Peening. (2016) - Závodská, Denisa; Guagliano, Mario; Bokůvka, Otakar; Trško, Libor
Abstract: It is well known that shot peening is able to increase the fatigue strength and endurance of metal parts, especially with a steep stress gradient due to a notch. This positive effect is mainly put into relation with the ability of this treatment to induce a compressive residual stress state in the surface layer of material and to cause surface work hardening[1] . In this paper shot peening is applied on the 40NiCrMo7 low alloy steel and subsequently the surface was re-peened with glass beads to decrease the final surface roughness. Roughness, hardness and residual stress analysis were used for characterizing the strongly deformed surface layer. Low frequency fatigue tests were carried out to evaluate the effect of the applied treatment on fatigue life in the high cycle region. Results show fatigue strength increase in the high cycle region after the shot peening surface treatment.